Analisis Hukum Terhadap Putusan Mahkamah Konstitusi Nomor 90/Puu-XXI/2023 Pasal 169 Huruf Q UU 7 Tahun 2017 Tentang Pemilu - Vagunaldi, Vagunaldi Vagunaldi; Widarto, Joko; Markoni, Markoni; Helvis, Helvis (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This thesis presents an in-depth legal analysis of the Constitutional Court (MK) Decision Number 90/PUU-XXI/2023 relating to the age requirements for presidential and vice presidential candidates as stipulated in Article 169 letter q of the Election Law. This study uses a normative legal method, in critically evaluating the legal standing of the applicant who questions the provisions of the article and the fairness of the decision that has been taken. Prior to the Constitutional Court's decision, the law required presidential and vice presidential candidates to be at least 40 years old. However, since this decision, the law has reinterpreted the age requirement not only as a minimum age of 40 years but also to include anyone who has or is currently holding a regional head position elected through general elections. This interpretation potentially expands the criteria in the election law. This decision also marks a significant shift in the role of the Constitutional Court from negative legislature to positive legislature, where previously the Constitutional Court only assessed the constitutionality of existing regulations without changing the substance of the law, the court actively formulated and determined new legal norms through its interpretation. This change not only opens up space for qualified candidates, but also sparks debate about the extent to which the Constitutional Court should be involved in the formation of public policy. As well as questioning the division of powers stated in the 1945 Constitution between the legislative, judiciary and executive within the framework of the Indonesian rule of law which has been the subject of criticism because it is considered to accommodate political interests more than legal interests